Week Days Symbolics in Paremiologic Fund of the French Language (Proceedings of Southern Federal University. Philology, 2018)
Ekaterina A. Nazarova (Rostov-on-Don, Russian Federation)The article discusses groups of French Paremiological Units (FPU), thematically related to the days of the week. The task of the author is to assess the positive and negative attitudes of the French to certain days of the week, to identify the potential favorability for the development of events on any given day of the week.The study found that the French language community auspicious days are Saturday and Sunday. Adverse days include Monday, Wednesday, Thursday, Friday, and you should expect fatal events, the formation of any exceptional circumstances on Tuesday.The author distributes FPU, prescribing certain behavior on a particular day of the week into the following groups: FPU, which are advisory in nature; FPU, warning against various activities; FPU, strictly restrictive; FPU governing economic activity; FPU, describing weather phenomena and climatic features of different periods.Key words: paremiological unit, names of days of the week, French.DOI 10.23683/1995-0640-2018-4-107-114